“I Am I and My Bacterial Circumstances”: Linking Gut Microbiome, Neurodevelopment, and Depression - Lima-Ojeda, Juan M.; Rupprecht, Rainer; Baghai, Thomas C. (Frontiers in Psychiatry, 2017)
Recently, there has been renewed interest in the role played by microbiome in both human health and human disease. A correct equilibrium between the human host and their microorganisms is important for an appropriate physiological function. Extensive research has shown that microbes that inhabit the gastrointestinal tract—or gut microbiota—are involved not only in both nutritive and digestive activities, but also in immunological processes. Moreover, the gut microbiome influences both central nervous system (CNS) and energy homeostasis. An altered gut microbiome has been associated with the pathophysiology of different diseases, including neuropsychiatric disorders. Apparently, both environmental—diet, exposition to antibiotics and infections—and host-genetic factors have a strong influence on gut microbiome, modulating the risk for neuropsychiatric illness. Also, early life disruption of the microbiome-gut-brain (MGB) axis has been associated with an increased risk of developing depression later in life, suggesting a link between gut microbiome, neurodevelopment and depression. This review aims to contribute to this growing area of research by exploring the role played by the gut microbiome in neurodevelopment and in the etiology of the depressive syndrome, including nutritional, immunological and energy homeostasis approaches.